Disease severity enhancement by an esterase from non-phytopathogenic yeast Pseudozyma antarctica and its potential as adjuvant for biocontrol agents. Issue 1 (December 2018) - Ueda, Hirokazu; Kurose, Daisuke; Kugimiya, Soichi; Mitsuhara, Ichiro; Yoshida, Shigenobu; Tabata, Jun; Suzuki, Ken; Kitamoto, Hiroko
Abstract The phylloplane yeastPseudozyma antarctica secretes an esterase, named PaE, and xylanase when cultivated with xylose. We previously observed that the lipophilic layer of Micro-Tom tomato leaves became thinner after the culture filtrate treatment. The leaves developed reduced water-holding ability and became wilted. In this study, the purified enzymes were spotted on Micro-Tom leaves. PaE, but not xylanase, thinned the lipophilic layer of leaves and decreased leaf resistance to the phytopathogenic fungusBotrytis cinerea . Disease severity increased significantly in detached leaves and potted plants treated with the culture filtrate andB .cinerea spores compared with those treated with inactivated enzyme andB .cinerea alone. Spore germination ratios, numbers of penetrating fungal hyphae in the leaves, and fungal DNA contents also increased significantly on the detached leaves. Japanese knotweed (Fallopia japonica ), a serious invasive alien weed in Europe and North America, also became susceptible to infection by the rust pathogenPuccinia polygoni-amphibii var.tovariae following the culture filtrate treatment. The culture filtrate treatment increased disease development in plants induced by both phytopathogenic fungi. Our results suggest thatP .antarctica culture filtrate could be used as an adjuvant for sustainable biological weed control using phytopathogenic fungi.